YOUNG TEACHERS AND STUDENTS – INTELLECTUAL POTENTIAL OF MODERN LEGAL SCIENCE - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the purpose of the scientific article is to synthesize the results of the 2nd International Scientific and Practical Conference «Youth Science Forum», dedicated to the Day of Science and to clarify the role of young scientists and students as the intellectual potential of modern legal science. Methods: general and special scientific (special) methods were used to achieve the stated purpose. The use of these methods allowed to outline the problems of the formation and development of the intellectual potential of modern legal science. Results: despite numerous studies on this subject, modern conditions dictate the need for continuous improvement of scientific research, which is possible only with the continuous search for new ways and areas of intellectual potential and requires an in-depth theoretical study of this inexhaustible resource that can provide long-term innovative development of modern science, including legal ones. The conference participants recommend increasing the level of financing of science, which will increase the prestige of scientific work, the attractiveness of scientific activity for youth, increase the salary for young scientists, create favorable conditions for scientific creativity (financing, equipment, scientific environment, information, etc.). Discussion: assistance of young scientists who are just starting their research path, under the guidance of recognized professionals in the field of law, and forming of their ideas in very real scientific projects. An important precondition for the development of national legal education and science in a competitive environment is to ensure its innovative development as a way not only to stay afloat in the complex realities of the modern globalized world, but also to give an result that will provide an independent and decent place in the construction of a fair world law and order. The turbulence processes associated with rapid, often unpredictable changes in the external and internal environment, encourage scientists and law practitioners to improve innovation activity, based on finding effective ways to use intellectual potential, which is an inexhaustible source of continuous development and the ability to adapt to the modern requirements. A lot of research has been written about problems in modern legal science. At the same time, the main one is the lack of practice in modern legal education. However, it should be noted that considering legal science from the point of view of its practical result is not entirely correct, since lack of practice does not mean deprivation of cognitive and scientific status. The problem of reduced need in existing legal science achievements is, first of all, the impossibility of influencing modern legal realities. Here you can agree with the existing statement that real life and legal science are in different directions. For example, if we take the influence of domestic legal science on legislative activity, then it is minimal, since lobbyism and political decisions prevail here. Therefore, the problem of efficiency increasing of intellectual potential as an effective factor in the innovative development of legal science requires further scientific research.